Augmented reality robot-assisted radical prostatectomy with PROXIMIE: Preliminary clinical experience - Samy Cheikh Youssef; Bana Sabbubeh; Kaled Haram; Jonathan Noël; Abdullatif Aydın; Ben Challacombe; Fairleigh Reeves; Nadine Hachach-Haram; Prokar Dasgupta (Urology Video Journal, 2022)
Objective: Surgical training has digitally evolved in recent years owing to technological advancements such as the implementation of tele-mentoring. Tele-mentoring enables resident surgeons to receive instruction and guidance from experts remotely, given a suitable internet connection. It is hypothesised that this augmented reality (AR) enhances the learning experience and surgical performance, by the use of overlays to live streamed surgery. Patient and surgical procedure: This study evaluated the implementation of a novel AR platform for robot assisted radical prostatectomy (RARP) procedures, assessing participant opinions, efficacy, and safety through questionnaires. Additionally, we investigated the broader utility of surgical recording in a video labelling study. All ethical protocols and patient confidentiality was maintained during this study. Results: This preliminary research demonstrates favourable results on average for ease of use, audio, and video quality rated by both mentors and mentees (Above 4 out of 5 in all fields). Questionnaire fields assessing future uses in mentees, revealed that ‘mentoring for technically challenging cases’ and ‘assessment or revalidation of surgeons’ were useful. The use of RARP recordings for video labelling yielded high success in a novice student. Among 25 video recordings, the labelled video selected for assessment showed an accuracy score averaging 93.1% with a range of 85.6% - 100% across expert examiners. Conclusion: The use of an AR telementoring platform can assist in building competency safely in advanced level surgical trainees for RARP. The self-training of a novice student in the accurate segmentation of RARP video recording confirmed a high degree of accuracy is feasible. Further research across numerous surgical procedures with a cohort of students is mandated.